Price setting in France: new evidence from survey data - Claire Loupias; Roland Ricart (European Central Bank (ECB), 2004)
This paper reports the results of a survey conducted by the Banque de France during Winter 2003-2004 to investigate the price-setting behavior of French manufacturing companies. Prices are found to adjust infrequently; the median firm modifies its price only once a year. Price reviews are more frequent than price changes; the median firm reviews its price quarterly. Firms are found to follow either time dependent, state-dependent or both pricing rules. Moreover, the chosen interval of price reviews depends on the probability that changes in the firms' environment occur. Coordination failure and nominal contracts (either written or implicit) are the most important sources of price stickiness, while pricing thresholds and physical menu costs appear to be totally unimportant. Asymmetries in price stickiness are found to be different for cost shocks compared to demand shocks: prices are more rigid downward than upward for cost shocks, while the reverse is true for demand shocks.
Keywords: E31; D40; L11; 330; Inflation persistence; price rigidity; price-setting behavior; survey data